Mapping fifty-five years of somatic embryogenesis research: A bibliometric analysis of trends, global collaborations, and key advances across more than nine thousand articles - Pérez Molina, Junior Pastor (2025)
Somatic embryogenesis (SE) is a key tool in plant biotechnology. It enables the regeneration of plants from somatic cells through a series of well-characterized steps that resemble those of zygotic embryogenesis. SE has many applications in agriculture, forestry, and conservation. Since its discovery in the 1950s, SE research has grown considerably, driven by advancements in tissue culture and molecular biology. This study presents a bibliometric and text-mining analysis of SE research over the last 55 years [1970–2024], examining 9230 peer-reviewed articles from the Dimensions.ai database. The analysis revealed a substantial increase in SE publications over time, with more than 81% of articles published after 1995. The USA, India, and China emerged as the top contributors, collectively producing 31.8% of the total output. Leading journals, such as Plant Cell, Tissue and Organ Culture and Plant Cell Reports accounted for 21.4% of SE publications. Co-authorship networks highlighted the USA, India, and China as central global collaboration hubs fostering partnerships with Europe, Asia, and the Americas. Taxonomic analysis identified Poaceae, Pinaceae, and Fabaceae as the most studied families, representing 35.8% of articles published during the analyzed period. However, there have been recent surges in the studies of Arecaceae and Malvaceae over the last two decades. Key contributions to SE research include advancements in genetic mechanisms, tissue culture techniques, model systems, transcriptional networks, and transformation processes. This study analyzes trends, leading contributors, and research themes in somatic embryogenesis, highlighting its expansion, methodological advances, and increasing relevance in plant biotechnology over the past five decades.